Enhancing Students’ Speaking Ability Through Role Play Integrated with Interactive Digital Flashcards at a Thai Secondary School - Nadya Nabila; Tengku Winona Emelia (FKIP, Universitas Palangka Raya, 2026)
In Thai EFL classrooms, limited vocabulary knowledge, low confidence, and high speaking anxiety often hinder students’ oral participation and reduce opportunities for meaningful communication in English. These challenges highlight the need for instructional approaches that simultaneously strengthen vocabulary mastery and encourage active speaking practice in authentic contexts. This study aims to investigate the effectiveness of integrating role play with interactive digital flashcards to support students’ speaking ability in a Thai secondary school. The study employs a mixed-methods approach with a quasi-experimental design using a one-group pre-test and post-test model. Quantitative data are collected through speaking tests assessing fluency, pronunciation, vocabulary use, and interaction, while qualitative data are gathered through classroom observations to explore students’ engagement, participation, and responses during the learning process. The instructional treatment combines vocabulary preparation through interactive digital flashcards with communicative role-play activities to promote active language use, increase students’ confidence, and create a more engaging learning environment. It is expected that this integrated approach will improve students’ speaking performance and motivation. Furthermore, this study is expected to contribute to EFL speaking pedagogy by providing empirical insights into the integration of communicative strategies and digital vocabulary support in secondary school contexts.